Feeding Practices and Early Childhood Caries: A Cross-Sectional Study of Preschool Children in Kanpur District, India. (5th December 2013) - Prakasha Shrutha, Santhebachalli; Vinit, Grandim Balarama Gupta; Giri, Kolli Yada; Alam, Sarwar
Abstract : Background . Early childhood caries (ECC) is a public health problem due to its impact on children's health, development, and wellbeing. The objective of this study was to assess the caries experience in 3–5-year-old children and to evaluate the relationship with their mothers' practices regarding feeding and oral hygiene habits in Kanpur. Method . A cross-sectional survey was undertaken on 2000 (974 boys and 1026 girls) children aged 3–5 years from a random sample of preschools in Kanpur district, India. Dental caries experience was recorded using WHO criteria. A pretested questionnaire with 9 questions was used for collecting information regarding mothers' practices regarding feeding and oral hygiene practices. Chi-square test (χ 2 ) and Student's t -test were used for statistical analysis. Results . The prevalence of ECC was 48% with mean dmft of 2.03 ± 2.99. Boys (57%) were affected more than girls (43%) which was found to be statistically significant (P < 0.05 ). Caries prevalence was high and statistically significant (P < 0.05 ) among those who were breast fed for longer duration, during nighttime, those falling asleep with bottle, and those fed with additional sugar in milk. Conclusion . Determining the role of feeding practices on early childhood caries can help in the development of appropriate oral health promotion strategies.